Karakteristik Fermentasi, Kecernaan, dan Estimasi Metan Ternak Ruminansia yang Diberi Saponin : Kajian Kuantitatif - Syamsiyah, Dzorifatus; Suharti, Sri; Jayanegara, A. (Universitas Bengkulu, 2023)
The effect of using saponins on ruminants' performance differed from several published research data based on the level of saponins added to the feed. This research was conducted to analyze the effect of saponins on fermentation characteristics, digestibility, and estimation of methane in ruminants with a mixed model approach from published journal articles—a total of 127 studies from 32 journals national and international. The variable measured included the level of saponins (%), dry matter intake, Average Daily Gain (ADG), Dry Matter Digestibility (DMD), Organic Matter Digestibility (OMD), Crude protein (CP), Neutral Detergent Fiber (NDF), Acid Detergent Fiber (ADF), protozoa population, bacterial population, Volatile Fatty Acid (VFA), acetate/C2, propionate/C3, butyrate/C4, valerate/C5, acetate/propionate (C2/C3), NH3, pH, and methane gas production. The results showed that using saponins in ruminants increased ADG, CP, ADF, NDF degradation, Total VFA, and proportion of propionate. The addition of saponins level reduced the protozoa population, acetate proportion, and the ratio of acetate: to propionate (C2/C3). In contrast, feed intake and digestibility decreased with the administration of saponin. The bacterial population were similar among treatments, and methane production increased by increasing saponins. In conclusion, the administration of saponin level recommended is 0.3-3.1% of the total ration to improve performance and increase feed efficiency.